Outer Van Allen Radiation Belt Response to Interacting Interplanetary Coronal Mass Ejections - E. K. J. Kilpua; D. L. Turner; A. N. Jaynes; H. Hietala; H. E. J. Koskinen; A. Osmane; M. Palmroth; T. I. Pulkkinen; R. Vainio; D. Baker; S. G. Claudepierre (AMER GEOPHYSICAL UNION, 2025)
We study the response of the outer Van Allen radiation belt during an intense magnetic storm on 15-22 February 2014. Four interplanetary coronal mass ejections (ICMEs) arrived at Earth, of which the three last ones were interacting. Using data from the Van Allen Probes, we report the first detailed investigation of electron fluxes from source (tens of kiloelectron volts) to core (megaelectron volts) energies and possible loss and acceleration mechanisms as a response to substructures (shock, sheath and ejecta, and regions of shock-compressed ejecta) in multiple interacting ICMEs. After an initial enhancement induced by a shock compression of the magnetosphere, core fluxes strongly depleted and stayed low for 4 days. This sustained depletion can be related to a sequence of ICME substructures and their conditions that influenced the Earth's magnetosphere. In particular, the main depletions occurred during a high-dynamic pressure sheath and shock-compressed southward ejecta fields. These structures compressed/eroded the magnetopause close to geostationary orbit and induced intense and diverse wave activity in the inner magnetosphere (ULF Pc5, electromagnetic ion cyclotron, and hiss) facilitating both effective magnetopause shadowing and precipitation losses. Seed and source electrons in turn experienced stronger variations throughout the studied interval. The core fluxes recovered during the last ICME that made a glancing blow to Earth. This period was characterized by a concurrent lack of losses and sustained acceleration by chorus and Pc5 waves. Our study highlights that the seemingly complex behavior of the outer belt during interacting ICMEs can be understood by the knowledge of electron dynamics during different substructures.